2001
DOI: 10.1038/sj.onc.1204675
|View full text |Cite
|
Sign up to set email alerts
|

Genetic loci controlling susceptibility to γ-ray-induced thymic lymphoma

Abstract: is a susceptible strain for the development of gray induced mouse thymic lymphoma whereas MSM shows resistance. Association analysis of 220 backcross mice between the two strains using 67 markers was carried out to identify loci involved in the control of susceptibility. The genotype of mice with lymphoma showed excess heterozygosity relative to MSM homozygosity at D2Mit15 and D4Mit12 and was skewed toward MSM-derived alleles at D5Mit5. The P values in Mantel-Cox test were 0.0048 (D2Mit15), 0.0034 (D4Mit12) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 27 publications
2
40
1
Order By: Relevance
“…Genetic background is known to affect the latency of radiation-induced mouse lymphomas (Saito et al, 2001) and an effect of genetic background has also been demonstrated on susceptibility to the heritable effects of radiation exposure (Watson et al, 1997). We therefore investigated an additional set of about 40 tumors from p53 þ /À (129/Sv  C57BL/6) F1 hybrids that show, on average, a longer latency than those from pure 129/Sv animals.…”
Section: Effect Of Genetic Background On Pattern Of Genetic Changes Imentioning
confidence: 99%
“…Genetic background is known to affect the latency of radiation-induced mouse lymphomas (Saito et al, 2001) and an effect of genetic background has also been demonstrated on susceptibility to the heritable effects of radiation exposure (Watson et al, 1997). We therefore investigated an additional set of about 40 tumors from p53 þ /À (129/Sv  C57BL/6) F1 hybrids that show, on average, a longer latency than those from pure 129/Sv animals.…”
Section: Effect Of Genetic Background On Pattern Of Genetic Changes Imentioning
confidence: 99%
“…Although the radiation does not play so prominent role as chemical carcinogen in all human cancer causes, due to the application of nuclear technology in human production and life, especially in medical diagnosis and treatment field occupies a more and more special position, the potential hazards of radiation on humans are increasing. Therefore, research on the relationship between radiation and cancer has been the oncology, radiation biology, radiation protection and epidemiological research focus (Thompson et al, 1994;Sun et al, 1996;Yu et al, 2001;Wang et al, 2002 (Hattori et al, 1988;Yoshida et al, 1997;Nishimura et al, 1999;Saito et al, 2001). However, due to the presence of species, individual and organization-specific genetic differences, it is not yet established in vitro study using the theoretical model to evaluate its relationship with human tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous association study of g-ray-induced thymic lymphomas in backcross mice between BALB/c and MSM and in congenic mice demonstrated the presence of the susceptibility locus near D4Mit12; the BALB/c allele exhibited a dominance or codominance over the MSM allele (Saito et al, 2001). This BALB/c allele also provided susceptibility to MNU-induced thymic lymphomas (Sato et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…A congenic mouse line for D4Mit12 on chromosome 4 was obtained previously (Saito et al, 2001), which carried an MSM-derived chromosomal region spanning D4Mit9 and D4Mit203 (40 Mb). The original congenic mice were crossed with BALB/c mice and four subcongenic lines were obtained after genotyping with 15 microsatellite markers within this region.…”
Section: Mice Irradiation and Lymphoma Inductionmentioning
confidence: 99%
See 1 more Smart Citation